Priority directions of institutional provision of regional development in the conditions of war - Yu.Р. Kharchenko (Економіка, управління та адміністрування)
The article solves practical scientific tasks, conducts research on the institutional support of the territorial organization of farms, and provides theoretical justifications based on the achievements of the currently existing science, a generalization of the current legislation and implementation practice. The paper provides the development of practical recommendations for improving the mechanisms and methods of providing high-quality administrative services by local self-government bodies. The modern domestic system of providing administrative services from the point of view of convenience for private individuals is characterized by many shortcomings of an objective and subjective nature. The current mechanism for the provision of administrative services by public authorities needs serious refinement, development of new approaches and their approval, comparison with foreign practice in order to determine the most optimal. To eliminate the shortcomings in this context, what administrative services are, is analyzed in detail. One of the main conditions for the successful reform of the civil servants’ remuneration system is stable financial support. The issue of reforming the system of remuneration of civil servants will be resolved together with the issue of determining additional sources of funding. The costs of carrying out the mentioned reform can be covered, in particular, by increasing the efficiency of public administration and optimizing the number of employees of executive authorities and eliminating vacant positions. As a result of the conducted research, it was found that the reform of public administration involves increasing the efficiency of the provision of administrative services. The network of centers for the provision of administrative services is actively developing and the provision of electronic services is being introduced. However, the availability of services and the quality of service differ in different territorial communities. Obstacles to the integration of certain popular services into administrative service provision centers remain due to excessive centralization of powers to provide them.